In Vitro Cholesterol Reduction Activity Test Of 70% Ethanol Extract of Hiyung Cayenne Pepper Fruit (Capsicum frutescens L. var hiyung) Originating from Tapin South Kalimantan - Mu'mina Hayati; Rizaldi, Gusti; Saputri, Revita (Pharmacon: Jurnal Farmasi Indonesia, 2025)
Kalimantan Island has an endemic plants that holds potential as a medical one of them namely hiyung cayenne pepper fruit (Capsicum frutescens L. var hiyung) the local commodity of Tapin, South Kalimantan and known as the hottest pepper in Indonesia. It containts secondary metabolites and capsaicin that has potential to lower cholesterol. This study aims to identify secondary metabolite compounds and cholesterol-lowering activity of 70% ethanol extract of hiyung cayenne pepper fruit. Cholesterol lowering test was conducted in vitro by cholesterol complex formation method with FeCl3 using UV-Vis Spectrophotometer at maximum wavelength of 525 nm. The results of the phytochemical screening test showed positively contained alkaloids, triterpenoids, phenols, saponins, tannins and flavonoids. The result of cholesterol reduction test from concentrations of 20, 40, 60, 80, and 100 µg/mL were 53.62%, 58.30%; 64.19%; 70.02%; and 74.91%, respectively. So, the 70% ethanol extract of hiyung cayenne pepper fruit has the potential to reduce cholesterol with the lowest concentration being able to reduce cholesterol by more than 50%.